1957
DOI: 10.1021/ja01561a024
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Molecular Size and Structure on the Pyrolysis of Esters1,2

Abstract: The effect of molecular size on the ease of the pyrolysis of esters has been studied by py roly zing cyclohexyl formate and its homologs. Higher molecular weight esters decomposed at a lower temperature than the lower molecular weight homologs. The decrease, however, in the temperature of pyrolysis as the size of the esters increases in molecular size by one methylene group is not a regular decrease; rather, it decreases in a zig-zag fashion. Substituted cyclohexyl benzoates, with 'electronegative groups in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1971
1971
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This is a surprising result as it is generally considered that larger molecules fragment more readily than smaller ones. 10 The second and third methyl substituent at the a position, however, shows a steric acceleration effect. The relative rates in the pyrolysis of isopropyl esters are acetate (I):propionoate (II):isobutryrate (VI):pivalate (trimethylacetate) (VII)…”
Section: Discussionmentioning
confidence: 99%
“…This is a surprising result as it is generally considered that larger molecules fragment more readily than smaller ones. 10 The second and third methyl substituent at the a position, however, shows a steric acceleration effect. The relative rates in the pyrolysis of isopropyl esters are acetate (I):propionoate (II):isobutryrate (VI):pivalate (trimethylacetate) (VII)…”
Section: Discussionmentioning
confidence: 99%
“…Consequently the gas-phase elimination of these tu-haloesters appears to be solely subject to the steric acceleration. The present correlation implies that it is not possible to question the assumption where the rate of pyrolysis of esters follows the same sequence as acid strength [2][3][4][5][6].…”
mentioning
confidence: 99%
“…The transmission of electrons toward the more electronegative halogen may simul- taneously cause polarization of the Cp6+---06bond and, to a slight extent, a greater a-electron delocalization of the C=O group. Consequently, the partially negative charged oxygen atom of the acetate would find an increased resistance in stabilizing its p electrons toward the adjacent more r-bonded carbon of the C=O group (2). Therefore, the greater the electronegative character of the halogen substituent, the lesser the stabilization of the oxygen p electrons of the C,-0 bond toward the carbonyl carbon and the slower the reaction rate.…”
Section: Resultsmentioning
confidence: 99%
“…Bailey and Hewitt [l] showed that the extent of yield percent in the pyrolysis of twelve esters of 4-methyl-2pentanol was directly proportional to the pK, values of their corresponding carboxylic acids. ;\loreover, a qualitative estimation of the thermal decomposition of substituted cyclohexyl benzoates [2] gave a good correlation to the strengths of the 7 7~ and p-substituted acids, except for the esters of the o-sub-* Visiting Professor, Faculty of Medicine, Universidad Central de Venezuela, Caracas. stituted acids.…”
Section: Introductionmentioning
confidence: 99%